“It’s All True!” The Use of the Biographical Method in Research on Šavrinkas - Rogelja, Nataša (Two Homelands, 2014)
Grounded in ethnographic research on women’s labour migration between the hinterland and thecoastal towns of Istria in the first half of the 20th century, the text highlights the use of the biographical method. It presents the specific methodological approach used in the research on Šavrinkas, and the reasons for using this type of methodology, as well as the broader historical context of the use of biographical methods in anthropology. The intertwining of the research topic and methodology as well as the past and the present will be discussed. Both emphases are crucial for the understanding of undocumented or at best artistically interpreted lives of women egg-traders, as well as their echoes in thepresent, in which migrant women played a crucial role in the process of forming the heritage of the area.